Dermocosmetics in the management of acne vulgaris. Recommendations of the Polish Dermatological Society. Part II - Zegarska, Barbara; Rudnicka, Lidia; Narbutt, Joanna; Barańska-Rybak, Wioletta; Bergler-Czop, Beata; Chlebus, Ewa; Czarnecka-Operacz, Magdalena; Czuwara, Joanna; Kaszuba, Andrzej; Lesiak, Aleksandra; Nowicki, Roman; Owczarczyk-Saczonek, Agnieszka; et al. (Dermatology Review/Przegląd Dermatologiczny, 2023)
Acne vulgaris is the most common dermatosis among adolescents, but it can also affect adults. Acne lesions located on the face cause discomfort and lead to impaired quality of life for many patients. Acne is a dermatological condition with multiple causes and clinical manifestations, as well as varying degrees of severity. Dermatological treatment alone does not always bring good therapeutic effects, and occasionally it may result in symptoms of skin irritation. Therefore, using appropriate dermocosmetics is crucial in managing the condition. Dermocosmetics play a potentially important role in minimizing the adverse effects of acne medications, providing a synergistic effect by addressing other acne-causing factors and/or enhancing the efficacy of other treatment modalities, and protecting the skin against the adverse impacts of the exposome. In cases of mild acne, dermocosmetics can be used in monotherapy as an alternative to acne medications or for maintenance therapy. It is also advisable to combine dermocosmetics with topical or systemic therapies to achieve a synergistic effect or to prevent and reduce drug-induced adverse reactions. Dermocosmetics have keratolytic and anti-inflammatory properties, regulate sebum production, and help maintain the balance of the skin’s natural microbiome.